Strategi Guru Bahasa Arab dalam Mengimplementasikan Pembelajaran Interaktif berbasis Media Digital di MAN Kota Batu - Fatma Dewi Adjiji; M. Abdul Hamid; Nur Qomari; Indah Rahmayanti (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2026)
The transformation of Arabic language learning in the digital era requires teachers to optimally utilize digital media innovatively to enhance student engagement and comprehension. This study aims to explore teachers’ strategies in implementing interactive digital media-based learning, identify the challenges encountered, and examine the solutions applied at MAN Kota Batu. A descriptive qualitative approach was employed, with data collected through classroom observations, in-depth teacher interviews, and document analysis. The findings indicate that teachers employ various interactive media applications—including digital quizzes, interactive visual media, and online learning platforms—to promote active student participation. The main challenges include limited infrastructure, unstable internet connectivity, and teachers’ technical skills. The school addresses these issues by providing technology training, improving digital facilities, and optimizing available learning devices. This study confirms that interactive digital media-based learning can significantly enhance students’ motivation and understanding, provided that teachers’ strategies are implemented effectively and technical obstacles are addressed. The findings contribute to the development of digital technology-based teaching strategies for Arabic language learning in secondary schools and can serve as a reference for innovative instructional practices in the digital era.